Searching for site-specific design - Sigmarsdóttir, Gudrún Birna (2014)
Humans experience space in diverse ways; through their senses, observations and emotional attachments. People connect with their environment on individual and group basis and create a variety of structures, based on different meanings and experiences. Hence, our built environments represent different values and meanings. All human made structures represent history and tradition; they are signs of their time. (Tuan, 1977) As old structures and designs give way to modernising transformation, it is essential to respect and if possible to maintain some of this quality of the place and time. Consequently, a precise and detailed analysis of the nature, role, significance and value of a place pegged for re-construction has to be carried out.